Impaired Axonal Regeneration in Diabetes. Perspective on the Underlying Mechanism from In Vivo and In Vitro Experimental Studies - Sango, Kazunori; Mizukami, Hiroki; Horie, Hidenori; Yagihashi, Soroku (Frontiers in Endocrinology, 2017)
Axonal regeneration after peripheral nerve injury is impaired in diabetes, but its precise mechanisms have not been elucidated. In this paper, we summarize the progress of research on altered axonal regeneration in animal models of diabetes and cultured nerve tissues exposed to hyperglycemia. Impaired nerve regeneration in animal diabetes can be attributed to dysfunction of neurons and Schwann cells, unfavorable stromal environment supportive of regenerating axons, and alterations of target tissues receptive to reinnervation. In particular, there are a number of factors such as an enhanced activity of the negative regulators of axonal regeneration (e.g., phosphatase and tensin homolog deleted on chromosome 10 and Rho/Rho kinase), delayed Wallerian degeneration, alterations of the extracellular matrix components, enhanced binding of advanced glycation endproducts (AGE) with the receptor for AGE, and delayed muscle reinnervation that can be obstacles to functional recovery after an axonal injury. It is also noteworthy that we and others have observed excessive neurite outgrowth from peripheral sensory ganglion explants from STZ-diabetic mice in culture and enhanced regeneration of small nerve fibers after sciatic nerve injury in streptozotocin (STZ)-induced diabetic rats. The excess of abortive neurite outgrowth may lead to misconnections of axons and target organs, which may interfere with appropriate target reinnervation and functional repair. Amelioration of perturbed nerve regeneration may be crucial for the future management of diabetic neuropathy.